Narcissism and social motives: Successful pursuit of egosystem goals boosts narcissism. Issue 7 (2nd October 2020) - Sheldon, Kennon M.; Sedikides, Constantine; Ntoumanis, Nikos; Corcoran, Michael; Titova, Liudmila
ABSTRACT: We investigated the links between grandiose narcissism (agentic and communal) and social motives (social egosystem vs. social ecosystem). In Study 1, agentic narcissism was positively associated with egosystem (self-serving) motives, and was negatively associated with ecosystem (prosocial) motives, as assessed by explicit and more behavioral means. The pattern for communal narcissism was more complex, depending on mode of assessment. Striving for egosystem (vs. ecosystem) goals interacted with longitudinal goal-attainment to predict increases in agentic narcissism over 30 days. Study 2 replicated this interaction pattern in a longitudinal experiment, which randomly assigned participants to pursue either egosystem or ecosystem goals during one semester. We conclude that grandiose narcissism is associated with social goals that can maintain or even further augment narcissism.